Atención primaria: factores asociados a la calidad de manejo del paciente politraumatizado - Neira Tacure, Marco Geovanny (2020)
Polytraumatized patients are considered a public health problem worldwide because they represent 12% of the global burden of disease in Latin America and in Ecuador, it is the third cause of death, the reason why it is considered opportune the analysis of the conditions and capacities that the health personnel possess for the care of polytraumatized patients because proper management will prevent complications and even death. For this reason, a descriptive study of a quantitative cross-sectional approach was developed at the Type C Health Center in Catamayo. The results show that although it is a newly established Centre (three years). The highest percentage that works in the emergency area of the Catamayo Health Centre are doctors, followed by nurses with an average age of 38 years and the highest percentage is female, it is verified that 79.2% (n = 19) of the Health Personnel apply adequate protocols for the management of patients with multiple injuries, 100% (n = 24) have full knowledge of ATLS (Advanced Life Support in Trauma) and 58.4% (n = 14) have the necessary knowledge to care for politraumatized patients. Furthermore, it could be determined that the Centre is constantly training health personnel because 45% (n = 11) receive training every 6 months and 44.2% (n = 10.6) every year. The highest percentage of patients attended were male who had no complications and also had a low mortality rate, this has allowed 98.7% (n = 74) of patients to have no complications and there is only 1.3% (n = 1) of deaths. Keywords: polytraumatized, quality of care, risk factors.